Preterm Retinopathy of Prematurity and risk factors from a tertiary health care unit: A descriptive study - Vura U V Nagajyothi; Karunakar Gare; Murali krishna Thummakomma; Mohan Amgothu; Guguloth Latha; A Kalyani; T Jaya Chandra; Prathap G (Perspectives In Medical Research, 2023)
Introduction: Retinopathy Of Prematurity (ROP), is the major preventable blindness in infants. A study was conducted to find the risk factors of ROP in premature infants with gestational age (GA) < 36 weeks.